Guest

In any triangle ABC, prove that a sin (B – C) + b sin (C – A) + c sin (A – B) = 0.

In any triangle ABC, prove that a sin (B – C) + b sin (C – A) + c sin (A – B) = 0.

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Welcome to AskIITians

In any triangle ABC,

a/sin A = b/sin B = c/sin C = k

a = k sin A, b = k sin B, c = k sin C

LHS

= a sin (B – C) + b sin (C – A) + c sin (A – B)

= k sin A [sin B cos C – cos B sin C] + k sin B [sin C cos A – cos C sin A] + k sin C [sin A cos B – cos A sin B]

= k sin A sin B cos C – k sin A cos B sin C + k sin B sin C cos A – k sin B cos C sin A + k sin C sin A cos B – k sin C cos A sin B

= 0

= RHS

Hence proved that a sin (B – C) + b sin (C – A) + c sin (A – B) = 0.

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free